Test analysis of anti-shock ability of high hardness polyurea-coated FRC composite structure - Zhao Pengduo (Zhongguo Jianchuan Yanjiu, 2019)
[Objectives] To analyze anti-shock ability of the composite structure whose base metal is coated with polyurea,[Methods] we obtained ballistic limit velocity by using a 12.7 mm ballistic gun and obtained the limit specific absorption ability of the composite structure under different conditions. In addition,by examining the macroscopic damage form of target plate structure,we discussed the advantage and disadvantage of two different polyurea structures in terms of anti-shock ability. We also make comparison to soft polyurea composite structure to verify the optimum anti-shock performance of hard polyurea-coated composite structure.[Results] The results show that the anti-shock ability of soft polyurea composite structure is the best when the polyurea coating is coated on the back of target;the anti-shock ability of hard polyurea composite structure is the best when the polyurea coating is coated on the front of target;furthermore,the anti-shock ability of the composite structure with the two types of polyuria coating as the front coating is better than when the coating is on the back surface and double-face structure.[Conclusions] The high hardness polyurea can be used as the front protective coating for general engineering application which has the better protective effect.